Self-assembly of gold nanoparticles as colloidal crystals induced by polymerization of amphiphilic monomers - Zucchi, Ileana Alicia (2008)
The self-assembly of inorganic nanoparticles (NPs) into hierarchical structures on different length scales is one of the main aspects of "bottom-up" approaches to create materials with specific electronic, optical, or magnetic properties. We report a new procedure to generate and stabilize colloidal crystals formed by gold NPs during a polymerization reaction, leading to an amphiphilic physical gel. Dodecanethiol-stabilized gold NPs with an average diameter of 2 nm were synthesized and dissolved (0.15 wt %) in a stoichiometric mixture of diglycidylether of bisphenol A (DGEBA) and dodecylamine (DA). The polymerization of DGEBA with DA was carried out at 100°C leading to a linear polymer that very slowly generated an amphiphilic physical gel by the self-assembly of dodecyl chains. The formation of the physical gel was followed by rheometry and its structure investigated by SAXS. In the course of this polymerization, gold NPs were phase-separated generating colloidal crystals with dimensions varying from tens to hundreds of nanometers (TEM) and exhibiting a 3D hexagonal close-packed (HCP) structure (SAXS). The size of the gold NPs forming the colloidal crystals was about twice the original size, meaning that a coalescence process took place. This was confirmed by the increase in the intensity of the plasmon band in UV-visible absorption spectra. Partitioning and irreversible adsorption of large colloidal particles at the air-polymer interface were observed, leading to highly ramified fractal structures. This was explained by the high energy needed to remove large colloidal particles attached at the interface. The polymer precursors used in the present study may, in principle, be employed for different kinds of NPs stabilized by hydrophobic chains to generate dispersions of colloidal crystals in polymer gels or percolating fractal structures at the air-polymer interface. © 2008 American Chemical Society.